Achievement of ultra-high strength in 45Si2MnCr2Mo steel via efficient and low-energy tempering. (8th February 2022) - Yang, Ming; Chen, Xiao-Hua; Wang, Zi-Dong; Chen, Kai-Xuan; Wang, Yan-Lin; Chen, Ming-Wen; Zhu, Yu-Zhi
Abstract: In this study, 45Si2MnCr2Mo steel was fabricated by casting, hot rolling, and normalizing, followed by tempering at different temperatures from 180 to 520 °C for 2 h. Special attention was paid to the effects of tempering on the microstructure and mechanical properties of the steel. The results indicate that microstructure of tempered steel consists of bainite, martensite, and retained austenite (RA), and it is not sensitive to tempering at temperatures below 320 °C. However, after tempering at temperatures of 420 and 520 °C, bainitic ferrite plates merged and their lath boundaries became vague. In turn, RA decomposed, whereas carbide particles appeared and then coarsened. With increasing tempering temperature, the volume fraction of RA achieved its peak value at 320 °C and carbon concentration within RA attained its peak value at 420 °C. The optimal balance of ultimate tensile strength of 2306 MPa and total elongation of 8.24% in the steel were achieved after being normalized at 950 °C for 0.5 h and subsequent tempering at 220 °C for 2 h. These values are found to exceed those of air-cooled and isothermal bainitic steels. Finally, the correlation between microstructure and mechanical properties of the steel under consideration was discussed.